Chronic total occlusions (CTO) in the field of Percutaneous Coronary interventions (PCI) is a challenge- the result of initial 25 cases. - Uddin, MIR Jamaal; Ali, M; Islam, KhQ; Choudhary, AHK; Salam, MA; Rahman, MF; Ali, M Atabar; Raisuddin, M; Islam, M Saiful; Shahabuddin, M (Nepalese Heart Journal, 2004)
With an aim to investigate the success rate & immediate clinical outcome of Percutaneous Coronary intervention (PCI) for chronic total occlusion (CTO). we analyzed PCI of 150 cases. This is an on going study started from April 2002 to till date. The technique of PCI involving CTO has improved over time. However limited data on acute & follow up result in patients treated with PCI on CTO in recent years are available. Our of 150 cases of PCI, 25 patients were of CTO of > 30 days of duration. The result of their PCI were evaluated. The age range of the Pts were 50±10 yr; with male female ratio of 5:1 Diagnosis of the Pts were old myocardial infarction with Post MI angina 20 cases, Chronic stable angina 5 cases. Single vessel disease was 20 cases & Double vessel disease was 5 cases. Angiographic success rate was 20 cases (80%), Procedural success 19 cases (76%), Clinical success 18 cases (70%).